Łaciński przekład rozprawki Pseudo-Arystotelesa Peri\ tw=n a)retw=n kai\ kakiw=n Franciszka Tidicaeusa, profesora Gimnazjum Akademickiego w Toruniu - Dreikopel, Tomasz (Folia Toruniensia, 2019)
The article discusses selected passages from the Latin translation of the essay On Virtues and Defects published at the beginning of the 17th century and attributed to Aristotle. The work was translated by Francis Tidicaeus, a professor at the Academic Junior High School in Toruń. The analysis sheds much light on the details of the Toruń scholar's translation workshop and allows us to show his methodology of work on the Greek original.